6x-3=4x+3+2x

Simple and best practice solution for 6x-3=4x+3+2x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x-3=4x+3+2x equation:


Simplifying
6x + -3 = 4x + 3 + 2x

Reorder the terms:
-3 + 6x = 4x + 3 + 2x

Reorder the terms:
-3 + 6x = 3 + 4x + 2x

Combine like terms: 4x + 2x = 6x
-3 + 6x = 3 + 6x

Add '-6x' to each side of the equation.
-3 + 6x + -6x = 3 + 6x + -6x

Combine like terms: 6x + -6x = 0
-3 + 0 = 3 + 6x + -6x
-3 = 3 + 6x + -6x

Combine like terms: 6x + -6x = 0
-3 = 3 + 0
-3 = 3

Solving
-3 = 3

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| (2x-6)+(x-3)= | | 20x-8=11x+2 | | 2x-5=x-(5x-7) | | 8(5+t)-6(t+2)= | | 4x+10x=10 | | -0.7x-1.75=1.7+0.8x | | 8(-1)-18= | | 2x-5=x-(5-7) | | 1.24*0.2= | | -14u+2u+12u+-u=16 | | -5n-2n=13 | | -5.2q+1.9=-27.8-1.9q | | 3x^7+2x^5-4x^3+6x^2+9=0 | | 15x^2+60x=55 | | -3=(-6)-n | | 2y+1-17=-2y+4 | | 4x-2+3x+2+5x=180 | | 7x+33+8x-18= | | -5y+4= | | 8(2+8n)-7(n-8)=72 | | 9x^2=-36x | | 45=n-54 | | 8b-12=-2 | | 6q-3=15 | | 24p-36=99+9p | | 96=4m | | 2y+1-17=-2-4 | | 5(5-k)-7(7+k)=0 | | 13-(x+6)=5x-5 | | 3.6x=4.2 | | 13u-10u=18 | | 3x-5x+8=8x-2x |

Equations solver categories